THE EFFECT OF CLASS SIZE AND OVER ON THE ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENT - HARENDRA RAM (International Journal of Multidisciplinary Research and Studies, 2021)
Similar to how the size of the class has dramatically increased, a balloon filled with air expands and finally explodes. Class size is a persistent problem in education, and it is rising in many districts. With a very visible 36, what was previously a typical classroom at age 29 is now overcrowded. Large classrooms may have a detrimental impact on students' academic performance, according to researchers and educators. This is made up of a decline in the academic performance of students in bigger classrooms and an improvement in the academic performance of students in smaller classes. The argument is that larger classrooms provide teachers less one-on-one time with each student, which results in less instruction time and poorer test scores. Additionally, it is implied that because there are more pupils in a larger class, disciplinary issues increase. Contrarily, in a smaller class, pupils are given more instructional time and are better able to concentrate on the material being taught rather than discipline or other problems going on in the room. According to research, student success is increased by reduced class sizes. Therefore, it is crucial to look at class size and how it influences learning.